Proactividad de las secretarias y su incidencia en el ejercicio laboral del GAD Parroquial Isla de Bejucal - García Montes, Sadid Anabella (2020)
This case study is based on describing, investigating and carrying out an analysis in reference to the topic: proactivity of the secretaries and its incidence in the work of the GAD institution belonging to Isla de Bejucal, which aims to propose solutions to the problems exposed in said study. For this, the deductive method was used through which relevant information was obtained ranging from the general to the particular, however, for data collection a questionnaire was prepared and a survey was applied to the secretaries of said institution with the in order to collect and analyze the information obtained. It should be noted that the main objective of the research is to analyze how the proactivity of secretaries affects their work practice. As such, the results obtained from said analysis are described; The proactive attitude is one of the main behaviors that the entire organization must take into account when hiring a secretary, so the proper functioning of the institution depends on them, allowing it to achieve achievements for the benefit of the same and exercise the work activities in a comprehensive manner and giving the user the attention they deserve, assertively communicating any concerns they may present.